Evolution - Barton, Nicholas H (New York : CSHL Press, 2007)
This extensively illustrated, full-color textbook is divided into five sections: Introduction: discusses the key experiments and ideas in the development of molecular biology and provides an account of the development of the ideas underpinning evolutionary theory. Origin and Diversity of Life: describes the history of life on earth from the origin of life to the evolution of humans, with emphasis on the major transitions in genetic organization, novel adaptations, and the diversity of life. The impact of molecular biology is clearly presented, with chapters that make extensive use of up - to - date insights gained from complete genome sequences and the molecular mechanisms of developmental biology. Evolutionary Processes: describes the evolutionary processes that account for the diversity of life: how variation arises and how selection acts on it are considered in detail. Many examples used to illustrate the theory are drawn from molecular sources. Human Evolution: discusses human evolution and diversity. The benefits molecular markers have conferred on the understanding of human evolution are highlighted and integrated with paleontological evidence. Methods and Tools: deals with techniques and models used in studying evolutionary biology, emphasizing the contribution of molecular biology and genomics to the phylogenetic reconstruction methods described. Recommended as a primary textbook for undergraduate courses in evolution. Required reading for biologists seeking a clear, current, and comprehensive account of evolutionary theory and mechanisms. Written by experts in population genetics, bacterial genomics, paleontology, human genetics, and developmental biology. Integrates molecular and evolutionary biology in ways that reflect current directions in research. Resources for Teaching Staff: The Evolution web site (www.evolution-textbook.org) is an invaluable supplement to the textbook, a resource for the teacher that contains downloadable figures (for PowerPoint or overhead display) and chapter problems. Visit the Evolution web site now for more information about this new book. Request a detailed Table of Contents, Sample Chapters, Exam Copies, and Updates about Evolution. Contents: Aim and Scope of the Book; I INTRODUCTION 1 The History of Evolutionary Thinking; 2 The Origin of Molecular Biology; 3 The Evidence for Evolution; II ORIGIN AND DIVERSIFICATION OF LIFE: 4 The Origin of Life; 5 The Last Universal Common Ancestor and the Tree of Life; 6 Diversification of Bacteria and Archaea. I: Phylogeny and Biology; 7 Diversification of Bacteria and Archaea. II: Genetics and Genomics; 8 Origin and Early Evolution of Eukaryotes; 9 Diversification of Plants and Animals; 10 Multicellularity and the Evolution of Body Plans; 11 Evolution of Developmental Programs; III EVOLUTIONARY PROCESSES: 12 Generation of Variation by Mutation and Recombination; 13 Variation in DNA and Proteins; 14 Variation in Genetically Complex Traits; 15 Random Drift; 16 Population Structure; 17 Selection on Variation; 18 The Interaction between Selection and Other Forces; 19 Measuring Selection; 20 Phenotypic Evolution; 21 Conflict and Cooperation; 22 Species and Speciation; 23 Evolution of Genetic Systems; 24 Evolution of Novelty; IV HUMAN EVOLUTION: 25 Human Evolutionary History; 26 Population and Medical Genetics; 27 Controversies and Speculations in Human Evolution; V METHODS AND TOOLS: 28 Phylogenetic Reconstruction; 29 Models of Evolution; Photo Credits; Index.
Includes bibliographical references; Glossary 783-801p; Index 811-833p
Keywords: Environmental Biology